Defense Mechanisms Employeed Adopted Teenagers in The Novel Far From The Tree (2017) by Robin Benway - Lola Viona; Delvi Wahyuni (Universitas Negeri Padang, 2022)
This research to see the extent of Robin Benway's novel Far From the Tree (2017) raises the issue of defense mechanisms. The defense mechanism refers to characters who face problems with their status as adopted children. The three teenage characters in the novel experience different problems because they are adopted by different families. This analysis is related to the theory of psychoanalysis put forward by Phebe Cramer (2008). The use of theory was based on the interpretation in the text and context of the novel. The data was collected from the quotation in the novel. The data collection was in the form of sentences and paragraphs. This research is qualitative research. In this study, the defense mechanism was examined in the novel Far From the Tree. The results showed that the character of adopted adolescents uses defense mechanisms as a form of self-protection from the problems they face.